Neurotensin receptor 1 is a new therapeutic target for human undifferentiated pleomorphic sarcoma growth. Issue 12 (3rd September 2019) - Tokumoto, Hiroto; Setoguchi, Takao; Saitoh, Yoshinobu; Sasaki, Hiromi; Nagano, Satoshi; Maeda, Shingo; Tanimoto, Akihide; Taniguchi, Noboru
Abstract: Undifferentiated pleomorphic sarcoma (UPS) is the second most common soft tissue sarcoma. For patients with unresectable or metastatic disease, chemotherapies are considered, but in many cases they are not curative. There is a need to identify specific molecular dysregulations that can be therapeutic targets. We focused on neurotensin receptor 1 (NTSR1), which belongs to the G‐protein‐coupled receptor. NTSR1 expression was upregulated in specimens from patients with UPS. Real‐time polymerase chain reaction showed that expression of NTSR1 messenger RNA was 5‐ to 7‐fold increased in UPS cells compared with myoblasts. Western blot showed a high expression of NTSR1 protein in UPS cell lines. Knockdown of NTSR1 prevented UPS cell proliferation and invasion. We confirmed that SR48692, an inhibitor of NTSR1, exhibited antitumor activities in UPS cells. The combination index showed that SR48692 and standard chemotherapeutic drugs prevented UPS cell proliferation synergistically. Mouse xenograft models showed that SR48692 inhibited extracellular signal‐regulated kinase phosphorylation and enhanced the response to standard chemotherapeutic drugs. Inhibition of NTSR1 improved the effect of standard chemotherapeutic drugs for UPS. SR48692 may be a new drug for targeted UPS therapy.